Evaluation of Cutaneous Spatial Resolution and Pressure Threshold Secondary to Digital Nerve Repair. Issue 4 (April 2016) - Klein, Holger J.; Fakin, Richard M.; Ducommun, Pascal; Giesen, Thomas; Giovanoli, Pietro; Calcagni, Maurizio
Abstract : Background: As the sophistication of functional reconstruction procedures continues to increase, so does the need for valid, precise, and reliable instruments to assess their clinical results. The authors compare two tests for spatial resolution and two for cutaneous pressure threshold in an adult patient cohort having undergone microsurgical digital nerve repair after traumatic transection. Methods: Patients who underwent epineural coaptation after digital nerve transection at the authors' institution between June of 2006 and December of 2011 were asked to participate in a follow-up examination assessing spatial resolution (two-point discrimination and grating orientation test) and cutaneous pressure threshold (Semmes-Weinstein monofilament test and pressure-specifying sensory device). Interinstrument correlations were conducted and critically elucidated. Results: Eighty-one patients (26 female and 55 male patients; median age, 42 years; interquartile range, 23 years) were examined with a mean follow-up period of 3.5 ± 1.4 years. Although all tests could differentiate between the healthy and operated fingers, poor to moderate correlations were found between two-point discrimination and grating orientation test (ρoperated = 0.483, p < 0.0001; ρhealthy = 0.350, p < 0.0001), and between Semmes-Weinstein monofilament test and Pressure-Specified Sensory Device testing (ρoperated = 0.287, p = 0.01; ρhealthy = 0.382, p < 0.001), indicating that they measure different properties. Altogether, the grating orientation test proved superior to two-point discrimination, whereas Pressure-Specified Sensory Device testing was superior to Semmes-Weinstein monofilament testing. Conclusions: Thoughtful use of test instruments is advisable when assessing sensibility of the hand. This study suggests including Pressure-Specified Sensory Device testing to assess cutaneous pressure threshold and the grating orientation test to assess spatial resolution in clinical, routine test batteries. CLINICAL QUESTION/LEVEL OF EVIDENCE: Diagnostic, III. Abstract : Supplemental Digital Content is available in the text.